Analisis Kinerja Perpustakaan SMKN 2 Bandung menggunakan Pendekatan Balanced Scorecard - Dimas Saputra; Angga Hadiapurwa; Yayu Wulandari (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2025)
This study aims to evaluate the performance of the SMKN 2 Bandung library using the Balanced Scorecard (BSC) framework. The research method employed is a case study with a qualitative, descriptive design. Data were collected through the BSC instrument, observation, and in-depth interviews. Informants were selected using a purposive sampling technique, which included the principal, librarian, and students. Data analysis was conducted using thematic and descriptive analysis methods. The study's results indicate several significant challenges across the four BSC dimensions. The financial sector shows that library funding accounts for less than 5% of the school budget, which is primarily focused on textbooks, neglecting facilities, staff training, and digital infrastructure. The customer dimension recorded 41.94% of students complained about a lack of non-academic books (motivational, history) and an inconvenient location, although 54.84% were satisfied. Internal processes were hindered by the SLIMS digital system (one computer for 2,000 students), which hampers e-book access, as well as inefficient asset management. The learning and growth section revealed that one librarian was managing 2,000 students (far from the ideal ratio of 1:500) and lacked technical training. This study concludes that the library performance of SMKN 2 Bandung is suboptimal. This performance is hampered by critical challenges across all four dimensions of the BSC, negatively impacting its support for vocational education. The study recommends strategic improvements, including reallocating funds for digital facilities and infrastructure, diversifying collections to reflect student interests, and enhancing human resource capacity through recruitment and technical training.